23 Июн 2021 в 19:47
34 +1
0
Ответы
1

To simplify the given expression, we can start by applying the double angle formula for sine and cosine:

sin(2x) = 2sin(x)cos(x)
cos(2x) = cos^2(x) - sin^2(x) = 1 - 2sin^2(x)

Now we can substitute these expressions into the given equation:

2sin(x)cos(x) + 2(2sin(x)cos(x)) + 3(1 - 2sin^2(x)) = 0

Rearranging terms, we get:

2sin(x)cos(x) + 4sin(x)cos(x) + 3 - 6sin^2(x) = 0

Combining like terms:

6sin(x)cos(x) - 6sin^2(x) + 3 = 0

Dividing the entire equation by 3:

2sin(x)cos(x) - 2sin^2(x) + 1 = 0

Using the double angle formula for sine once again:

2sin(x)cos(x) - sin^2(x) + cos^2(x) = 0

sin^2(x) + cos^2(x) = 1

Therefore, the simplified expression is:

1 = 1

So, the given equation simplifies to 1 = 1, which is always true.

17 Апр в 15:50
Не можешь разобраться в этой теме?
Обратись за помощью к экспертам
Название заказа не должно быть пустым
Введите email
Бесплатные доработки
Гарантированные бесплатные доработки
Быстрое выполнение
Быстрое выполнение от 2 часов
Проверка работы
Проверка работы на плагиат
Интересные статьи из справочника
Поможем написать учебную работу
Название заказа не должно быть пустым
Введите email
Доверьте свою работу экспертам
Разместите заказ
Наша система отправит ваш заказ на оценку 84 848 авторам
Первые отклики появятся уже в течение 10 минут
Прямой эфир